Counseling to improve mental health of the elderly community in Kertorejo, Malang Regency - Minarni Wartiningsih; Hanna Tabita Hasianna Silitonga; Ni Njoman Juliasih; Charles Siahaan; Imelda Ritunga; Eric Dino Tandoyo; Kevin Cerwyn Dedwydd; Chindy Claudya Angriyanto; Risa Mauludia; Alvionita Muntholib; Aren Lestyani; Timothy Tobias (University of Merdeka Malang, 2022)
Elderly is any person aged 60 years or more, who physically looks different from other age groups. A person experiences some decline in body functions. Mental disorders are also often experienced by the elderly, including stress, depression, and anxiety so that the elderly have the potential to hurt themselves. Therefore, elderly counseling and elderly exercise are expected to be the solution. The purpose of counseling about physical activity and mental health of the elderly and elderly gymnastics is to improve the mental health of the elderly in Kertorejo Village, Malang Regency, East Java Province. The methods used during the activity are active participation, lectures, question and answer discussions, document searches, and literature studies. The stages of this community service are (1) Data collection of elderly profiles in Kertorejo (2) Counseling on physical activity and mental health of the elderly, (3) Filling out pre-intervention questionnaires, (4) Elderly exercise, and (5) filling out post-intervention questionnaires. The result of this community service activity was a decrease in the level of mental health of the elderly in Kertorejo after the intervention was measured by comparing the results of pre and post intervention questionnaires.